Empowerment of Economy and Finance Through Digital Literacy Training in Sorong City - Kahina, Dwi Iin; Rokhimah, Rokhimah; Hasrun, Andi; Masseni, Masseni; Sofia, Susetyowati (Teumulong: Journal of Community Service, 2024)
In Sorong City, West Papua, financial and digital literacy challenges are still the main obstacles in utilizing full economic potential, especially for Micro, Small and Medium Enterprises (MSMEs). This study aims to evaluate the effectiveness of digital and financial literacy training programs designed to increase the economic independence of local communities. This study uses quantitative and qualitative methodologies to collect and analyze data related to capacity building and implementation of post-training financial and digital literacy knowledge. The results of the study are expected to provide valuable insights into the effect of training on improving the digital and financial skills of Sorong residents, as well as its contribution in expanding access to markets and information networks.